Java Script - Negrino, Tom.; Smith, Dori. (New Delhi : Dorlong Kindersley, 2011)
With the release of Adobe Creative Suite CS5, Dreamweaver solidifies its role as the de facto tool of choice for anyone designing for the Web. Adobe Dreamweaver CS5 for Windows and Macintosh: Visual QuickStart Guide uses a combination of task-based instruction and strong visuals to teach beginning and intermediate users how to create, design, and publish powerful, innovative Web sites with Dreamweaver. Leading technology authors Tom Negrino and Dori Smith take you step-by-step through the new features in Adobe Dreamweaver CS5, with completely revised chapters on critical tools like styling pages with CSS and adding user interactivity with JavaScript dynamic elements. You'll also learn to take advantage of Dreamweaver's new ability to build and modify sites that use popular content management systems, such as WordPress, Joomla!, and Drupal. If you're new to Dreamweaer and web design, you'll learn to create your first Web site, add text, style and lay out page content, manage styles, work with links, incorporate images, media, tables, forms, and frames, design site navigation, and so much more. If you're an experienced user, you'll find this a convenient reference to the new features of Dreamweaver CS5. Note from the publisher: FREE Adobe Dreamweaver CS5.5 updates are available for this title. Simply register your product at www.peachpit.com/register and you will receive the updates when they become available.